2016
DOI: 10.1021/acs.jmedchem.6b00356
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure–Activity Relationships of a Highly Selective Butyrylcholinesterase Inhibitor by Structure-Based Virtual Screening

Abstract: Structure-based virtual screening of two libraries containing 567 981 molecules was used to discover novel, selective BuChE inhibitors, which are potentially superior symptomatic treatments in late-stage Alzheimer's disease. Compound 16 was identified as a highly selective submicromolar inhibitor of BuChE (huBuChE IC50 = 0.443 μM) with high permeability in the PAMPA-BBB model. The X-ray crystal structure of huBuChE in complex with 16 revealed the atomic-level interactions and offers opportunities for further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 41 publications
1
84
0
1
Order By: Relevance
“…The inhibitory activity of the selected EOs on acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) cholinesterase (ChE) were studied since these enzymes have a fundamental role in the nervous system, as they are responsible for the hydrolysis of ACh [87]. L. officinalis and M. pulegium EOs, both rich in oxygenated terpenes, showed the highest inhibitory potency on AChE.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory activity of the selected EOs on acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) cholinesterase (ChE) were studied since these enzymes have a fundamental role in the nervous system, as they are responsible for the hydrolysis of ACh [87]. L. officinalis and M. pulegium EOs, both rich in oxygenated terpenes, showed the highest inhibitory potency on AChE.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Wu et al, synthetic compounds showed similar effectiveness in inhibiting BuChE from equine and human plasma, but with a higher potency over the human enzyme [39]. Similarly, Dighe et al have shown that their lead was 2-fold more potent in inhibiting human BuChE than equine BuChE [40]. In the same way, we could hope for a better activity in human BuChE.…”
Section: Characterization Of the Active Pharmaceutical Ingredient (Api)mentioning
confidence: 91%
“…Among these, donepezil and galantamine are selective AChE inhibitors, while rivastigmine is a dual AChE-BuChE-inhibiting compound. 17 The active site of human AChE is a long gorge with a length of approximately 20Å. Two key sites, namely the catalytic active site (CAS) at the bottom of the gorge and the peripheral anionic site (PAS) near the entrance of the gorge, are linked by a narrow groove.…”
Section: Introductionmentioning
confidence: 99%